Nexos e reflexos de uma experiência formativa mediatizada por ambiente virtual de aprendizagem: formação de professores de Ciências e Matemática na Amazônia - MARTINS, France Fraiha (Universidade Federal do Pará, 2012)
This is a qualitative narrative research, based on experiences of Amazon´s science and mathematics teachers in a distance education course that occurred in the context of a Virtual Learning Environment (VLE). The goal of this research is to Investigate how this formative experience is catalyst for teacher reflection on Amazon context of teaching science and mathematics, and which other learning results from such formation appears in different perceptions of teaching practice in this area at elementary schools. Nine were the subjects involved in research, which were selected according to the following criteria: being studentteachers from the post-degree course of science and mathematics education in EDUCIMAT program, that teach / taught science and mathematics; had a high level of involvement in interactions occurred in the AVA; expressed full reflexive ideas. As investigative tool, I chose to hear subjects evidences by means of semi-structured interviews that were recorded in audio and later transcribed. Besides the interviews, I used my field diary as an information source which was built during the search through perceptions of the subjects and their contexts, in addition to the records of various events within the search. Trying to produce new understandings of investigated narratives, I appropriate myself with Textual Analysis of the Speech as methods of empirical material analysis. Thus, systematizing subject’s manifestations taking into account the recurrences and singularities, such analysis gave way to three themes that I deal with in this research assuming the following headings: i) formation in the Amazon context: obstacles and confrontations, ii) technologies and VLE: sense(s) of formative experience and iii) the impact of experience on perceptions of teacher practice and formation. The analysis shows the difficulties of access to formation, information, technologies and cities in the Amazon inside, beyond the cost factor, as confrontations to form itself in that context. Moreover, the subjects show that when they exchange, experience and interact in the VLE, they gave way indicative of self pointing to (re) invention of itself, to set a world teacher marked by technological advances and to overcome the use of technologies that surprise and (trans)form. As a result of the analysis, the subjects announce knowledge developed through the formative experience that focus on other/new perceptions of their educational practices: the use of information and communication technologies as possible tools in addition to the interaction and exchange of experiences and dialogue in situations of teaching. The VLE, perceived by the subjects as an embedded resource for formation teachers at a distance, appears as an opportunity to continue formation made by the diversity of ideas and as a way of bringing up educational technologies in front of difficulties expressed by the subject.